OBJECTIVES AND PROBLEMS OF TEACHING PHILOSOPHY IN HIGHER EDUCATION - Elena V. Malakhova (Plekhanov Russian University of Economics, 2017)
The article shows philosophy teaching as an integral part of today's higher education. The author investigates methods used in teaching philosophy to students of non-philosophic specialties and identifies targets set for such teaching. By analyzing problems arising in the process of mastering philosophy the author formulates possible ways of their resolving proceeding from expectations and notions of the subject with which students start learning it. The principle task of philosophy, in our point of view is to help learners systematize their private outlook, which would provide an opportunity of further comprehension of philosophic issues in connection with scientific interests and professional orientation of students.